Pulmonary Arterial Hypertension In Congenital Heart Disease Could it be Normalized ? 11 years prospective study (2010-2021) - Feituri , Rasmia H.; El maadani, Mariam; El Megasbi, Hanan; Khazmi , Amal Khazmi; Nabous , Ibrahim (Scientific Journal of University of Benghazi, 2021)
Objective: To recognize the effect of early surgical intervention in congenital heart in improving pulmonary hypertension, and to show the result of using medication in decreasing pulmonary hypertension Background : Pulmonary hypertension is defined as a mean pulmonary arterial pressure ≥25 mmgh .in congenital heart disease (PAH-CHD)it is caused by pulmonary overcirculation, pulmonary vasoconstriction, and pulmonary vascular disease, either alone or in combination. Design prospective clinical trial study with follow up. Setting: Al-Hawary General Hospital, National Benghazi Cardiac Center. Methods: 68 patients have been seen with pulmonary hypertension due to congenital heart disease in the period from 6/2010- 6/2021, Age: from 6 months to 40 years old, We exclude 4 patients with primary pulmonary hypertension, we used clinical criteria, echocardiogram, and cardiac catheterization. Follow up method: period 3 months – 11 years, 4/68 patients lost their contact, we divide the other 64 patients into two the groups; Group 1 (n= 34) <2 years old , Group 2 (n= 30) >2 years old. Results: Gender: F: M ratio is approximately 1.3 :1. The type of congenital heart disease was in (48.5%)of patients VSD, in (28%) AVC, (8.5%)ASD, (4.5%) TPVDA, (3%) TGA, (3%) complex,(1.5%) univentricle, (1.5%) PDA,(1.5%) intramitral valve membrane MS. (34%) were Down syndrome patients, 37/68 received sildenafil , 1/68 Bosentan, and 3/68 received both drugs. Follow up results: Group 1 28/34 (82%) PHT normalized, 26/28 post operative, Group2 results:(10%) PHT normalized after surgery, Conclusions: The best therapy for PAH-CHD remains prevention through a “timely” repair of the defect., advanced medications are required.